Narrative Review of Parental Leave Policy: How is the Implementation and Impact on Child Development? - Firman, Nurinas Dzakiyah; Hermawan, Luthfia Ayu Rizky (Jurnal Psikologi, 2025)
The importance of adequate parental leave and childcare policies cannot be overstated, as they provide essential social protection for children and families. While most studies on parental leave policies focus on the impact of childbearing on women’s labour market participation, limited evidence is available regarding their effects on child development and well-being. Adopting a narrative review approach, this study examined the impact of parental leave policies on child development by analysing 10 empirical articles published within the past decade, retrieved from various databases and reviewed using an inductive analysis approach. Findings suggest that parental leave not only enables mothers to provide optimal care and strengthen the mother–child emotional bond but also encourages fathers to take an active role in childcare, which is critical for children’s cognitive and socio-emotional development. These insights highlight the need for policymakers to design inclusive parental leave policies that support both parents in providing the best possible care for their children.